2007
DOI: 10.1016/j.ejvs.2006.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Facial Cutaneous Cholesterol Embolism Revealing a Tight Carotid Stenosis: A Case Report

Abstract: We report a case of systemic cholesterol embolisms (CE) with rare localization to the level of the face from a tight carotid stenosis. The case history is that of a 75 year old patient who presented with cholesterol embolisms in the territory of the external carotid artery. The patient underwent successful carotid endarterectomy with no postoperative neurological event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Several reports show that patients with CCE have involvement of the carotid arteries as well as the aorta. 4,5 We examined carotid plaque characteristics and confirmed that carotid complex plaques can be a surrogate marker of systemic instability of patients with CCE.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports show that patients with CCE have involvement of the carotid arteries as well as the aorta. 4,5 We examined carotid plaque characteristics and confirmed that carotid complex plaques can be a surrogate marker of systemic instability of patients with CCE.…”
mentioning
confidence: 99%
“…Several reports show that patients with CCE have involvement of the carotid arteries as well as the aorta. 4,5 We examined carotid plaque characteristics and confirmed that carotid complex plaques can be a surrogate marker of systemic instability of patients with CCE.The second study was a prospective investigation of the relationship between ACP and CCE. In addition, we aimed to establish criteria for predicting ACP at high risk of leading to CCE.…”
mentioning
confidence: 99%